ANALYSIS OF THE IMPLEMENTATION OF PUBLIC HEALTH SERVICE POLICIES BASED ON POPULATION IDENTIFICATION NUMBERS IN BEKASI CITY: A LITERATURE REVIEW - Shelfie Prihantini; Janiscus Pieter Tanesab (SOSIOEDUKASI, 2026)
This study examines the implementation of the Community Health Service based on National Identification Number (LKM-NIK) policy in Bekasi City as a complementary policy to close protection gaps in Indonesia's National Health Insurance (JKN). Although Bekasi City has reached 99.87% or 2.592.517 persons (JKN-KIS) membership coverage and finances 386,389 beneficiaries through the local budget scheme (Juni 2026), this administrative achievement has not fully guaranteed substantive health protection for all residents. This study applies a descriptive qualitative approach using a Systematic Literature Review of 25 selected articles from Scopus. The findings show that LKM-NIK implementation is influenced by policy content clarity, targeting accuracy, financing sustainability, NIK data integration, cross-actor coordination, health facility capacity, and partner hospital compliance. From Grindle's perspective, the success of LKM-NIK is shaped by the interaction between policy content and implementation context. Therefore, LKM-NIK should be strengthened through accurate data governance, sustainable financing, clear public communication, and patient-experience-based evaluation.